South Korea's 70-year endeavor for foreign policy, national defense, and unification. (2018) - Nam, Sung-Wook; Rhee, Sang-Woo; Kim, Myongsob; Kim, Young Ho; Han, Yong-Sub; Chung, Young-Soon; Yoo, Seong-Ok
No abstract available